Using Remote Sensing Methods for the Three Lakes' and Evaluating Their Water Surface and Their Fluctuations - Ziaee, Ardeshir; Kapralova, Daria O. (CV. Literasi Indonesia, 2025)
Iran faces numerous environmental issues such as drought, population growth, war, air pollution, climate change, industrial and agricultural output, sanctions, excessive water consumption, and lax enforcement of environmental regulations. Climate change is thought to be one of the crucial factors of impact on water resources in the world. The research is focused on the lakes of Urmia, Namak, and Hamun, using satellite images from Remote sensing to estimate water areas within 10 (2015-2024) years, follow the changes, and analyze the reasons for these changes. Lake Urmia experienced a downward trend in water levels, despite increased precipitation and water rights allocation. Namak Lake showed a greater correlation with temperature fluctuations and precipitation. Hamun Lakes' water volume was more dependent on water rights and temperature fluctuations significantly impacted lake water levels. So all the lakes, located in different areas of the country did not show the same correlation with climate change. As the recovery plan for Lake Urmia seems to include the impact assessment of agricultural water consumption, Hamun Lakes seems to be more dependent on Afghanistan’s dams, only Namak Lake showed a good response to the precipitation values. The results of the work could be used by the authorities for the proper water management assessment.